2008
DOI: 10.1136/oem.2007.037655
|View full text |Cite
|
Sign up to set email alerts
|

Interpersonal conflicts at work as a predictor of self-reported health outcomes and occupational mobility

Abstract: The results of this study indicate a possible causal relationship between interpersonal conflicts at work and self-reported health and occupational mobility. Given the considerable impact of interpersonal conflicts at work on the individual worker and on the organisation, and the fact that interpersonal conflicts at work are highly prevalent, these findings underline the need for interventions aimed at preventing the occurrence of interpersonal conflicts at work, or at least reducing the harmful effects on bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 47 publications
1
34
0
Order By: Relevance
“…A comparison with a sample survey of the general Norwegian working population shows that the proportion "often" involved in interpersonal conflicts with superiors or co-workers was 8.5% and 2.8%, respectively (https://www.ssb.no/statistikkbanken). Two European studies found that such conflicts occurred for 7-9% (Appelberg et al, 1991b;Raeve et al, 2009). This indicates that the proportion of workers directly involved in conflicts in our sample was up to three times more frequent than in these comparison groups (21% vs. 7%).…”
Section: Discussionmentioning
confidence: 50%
See 3 more Smart Citations
“…A comparison with a sample survey of the general Norwegian working population shows that the proportion "often" involved in interpersonal conflicts with superiors or co-workers was 8.5% and 2.8%, respectively (https://www.ssb.no/statistikkbanken). Two European studies found that such conflicts occurred for 7-9% (Appelberg et al, 1991b;Raeve et al, 2009). This indicates that the proportion of workers directly involved in conflicts in our sample was up to three times more frequent than in these comparison groups (21% vs. 7%).…”
Section: Discussionmentioning
confidence: 50%
“…Some use a dichotomous variable, asking the respondents questions such as "have you had considerable difficulties with superiors/co-workers" (Appelberg et al, 1991b) or "do you have conflicts with your co-workers/daily supervisors" (Raeve et al, 2009), while others have asked workers "how often do you get into arguments with others at work/with your supervisor?" (Frone, 2000).…”
Section: Independent Variablesmentioning
confidence: 99%
See 2 more Smart Citations
“…The previous studies showed that a high degree of interpersonal conflict or workplace conflicts was associated with negative feelings, counter-productive manner, work incapacity among women, stress symptoms, increased risk for mental ill health and low self-reported health [14][15][16][17][18][19][20][21][22] .…”
Section: The Connection Between Interpersonal Conflict and Healthmentioning
confidence: 99%